Analisis Dan Perancangan Knowledge Management System Berbasis Android Pada SMPN 8 Kota Jambi - Efrima, Randa Bias; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2021)
Junior High School 8 Jambi City, which was founded in 1982, has a role as an educational institution that has the authority and duties in the development and implementation of education. Advances in technology and science are new challenges for schools that must manage integrated knowledge assets, sharing and innovation that will encourage the creation of knowledge management. The problem faced by SMPN 8 Jambi City is the unavailability of a system that can organize, manage, and disseminate knowledge properly and in a structured manner. In order for this problem to be resolved, a system that can manage existing knowledge is needed. In this study, researchers used the UML (Unified Modeling System) method as a design and development tool. This research resulted in a design of an Android-based Knowledge Management System that is able to identify, collect, documentation, manage and disseminate existing knowledge at SMPN 8 Jambi City.